Claudin-4 knockout by TALEN-mediated gene targeting in MDCK cells: Claudin-4 is dispensable for the permeability properties of tight junctions in wild-type MDCK cells. - Shinsaku Tokuda; Toyohiro Hirai; Mikio Furuse (PLoS ONE, 2017)
Epithelia act as a barrier between the internal and external environments, and the movement of substances via the paracellular pathway is regulated by tight junctions (TJs). Claudins are major determinants of TJ permeability. Claudin-4 was the first claudin whose involvement in the TJ permeability in cultured cells was directly demonstrated, but the permeability properties of individual claudins including claudin-4 are still incompletely clarified. In this study, we established claudin-4 knockout cells using transcription activator-like effector nucleases (TALENs), a recently developed method for genome editing, and investigated the permeability property of claudin-4 in MDCK II cells. We found that claudin-4 knockout has no apparent effect on the localization of other claudins and electrophysiological properties in MDCK II cells. Therefore we further established claudin-2 and claudin-4 double knockout clones and investigated the effects on TJs. Claudin-4 knockout in addition to claudin-2 knockout slightly increased the localization of other claudins at TJs but showed no obvious effects on the electrophysiological properties in MDCK II cells. These results indicate that claudin-4 is dispensable for the barrier property of TJs in wild-type as well as claudin-2 knockout MDCK II cells. Our results suggest the need for further knockout analysis to reveal the permeability properties of individual claudins.